Perspectives of the 13th National Congress on strengthening national defense and security to firmly protect the Socialist Vietnamese Fatherland - Bùi Quang Huy; Nguyễn Trọng Phượng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Strengthening national defense and security, firmly defending the Socialist Vietnamese Fatherland is an important and regular task of the Vietnamese revolution. The article summarizes the new perceptions and thinking in the Document of the 13th National Party Congress on the objectives and tasks of national defense and security to firmly protect the socialist Vietnamese Fatherland.